Implementasi Bantuan Hukum Litigasi dan Non Litigasi Melalui Lembaga Bantuan Hukum Universitas Lancang Kuning - Samariadi Samariadi; Robert Libra; Desi Ratnawati.S; Anisa Bulqis Zahra; Dewi Angle Caroline; Kevin Zuchri; David Carlos Bakara (Pusat Riset dan Inovasi Nasional, 2024)
Legal aid is a constitutional right for every citizen to ensure protection and equality before the law, as an effort to recognize Human Rights (HAM). Receiving legal aid is a manifestation of access to justice, which is the implementation of guarantees of legal protection and equality before the law. This principle is in line with the concept of legal aid which is related to the ideals of a welfare state. Legal aid also plays a significant role in the Criminal Justice System and the State Administrative Justice System as an integral part of protecting human rights for every individual, including the right to legal aid. This right is considered a very important right for every citizen, especially in the context of legal proceedings, especially criminal law and state administrative law, where the defendant cannot defend himself. The government has provided free legal aid for underprivileged people, but many are still not aware of this, causing them to feel that they are not supported by the government. This article details the realization of legal assistance related to both litigation and non-litigation cases related to the Lancang Kuning University Legal Aid Institute.